Tidal signatures in mesospheric turbulence - C. M. Hall; S. Nozawa; A. H. Manson; C. E. Meek (Annales Geophysicae, 2006)
We search for the presence of tidal signatures in high latitude mesospheric turbulence as parameterized by turbulent energy dissipation rate estimated using a medium frequency radar, quantifying our findings with the aid of correlation analyses. A diurnal periodicity is not particularly evident during the winter and spring months but is a striking feature of the summer mesopause. While semidiurnal variation is present to some degree all year round, it is particularly pronounced in winter. We find that the maximum in the summer 24-h variation corresponds to that of the westward phase of the diurnal tide, and that the maximum in the winter 12 h variation corresponds to that of the southward phase of the semidiurnal tide. This information is used to infer the horizontal propagation direction of gravity waves: during the summer the eastward direction is consistent with closure of the summer vortex, while in winter the inferred directions require more complex arguments.